A Developmental-Science Perspective on Social Inequality. (December 2020) - Elenbaas, Laura; Rizzo, Michael T.; Killen, Melanie
Many people believe in equality of opportunity but overlook and minimize the structural factors that shape social inequalities in the United States and around the world, such as systematic exclusion (e.g., educational, occupational) based on group membership (e.g., gender, race, socioeconomic status). As a result, social inequalities persist and place marginalized social groups at elevated risk for negative emotional, learning, and health outcomes. Where do the beliefs and behaviors that underlie social inequalities originate? Recent evidence from developmental science indicates that an awareness of social inequalities begins in childhood and that children seek to explain the underlying causes of the disparities that they observe and experience. Moreover, children and adolescents show early capacities for understanding and rectifying inequalities when regulating access to resources in peer contexts. Drawing on a social reasoning developmental framework, we synthesize what is currently known about children's and adolescents' awareness, beliefs, and behavior concerning social inequalities and highlight promising avenues by which developmental science can help reduce harmful assumptions and foster a more just society.